Oncocytoma: The Vanishing Parotid Mass - Patel, N.D. (AJNR Am J Neuroradiol, 2011)
Parotid gland oncocytoma is an uncommon, benign salivary neoplasm composed of mitochondria-rich oncocytes. The purpose of this study was to correlate MR imaging and histopathology of parotid gland oncocytomas and to define the features that may distinguish these neoplasms from other benign and malignant parotid gland tumors. The MR imaging features in 9 patients with a pathologic diagnosis of oncocytoma were retrospectively reviewed. The imaging features were strikingly similar for 8 of the 9 patients. All lesions appeared T1 hypointense but isointense to the native parotid gland on fat-saturated T2 and postcontrast T1 imaging. On MR imaging, parotid gland oncocytomas share specific imaging characteristics that have not been described for benign or malignant parotid gland tumors. Oncocytomas are isointense to native parotid gland on fat-saturated T2 and T1 postcontrast MR images. Preoperative identification of correct histology may help surgical planning.